We need to be more critical toward digital interventions for eating disorders: a commentary on McClure et al (2023) - Bauer, Stephanie; Moessner, Markus (The international journal of eating disorders, 2023)
Over the past two decades, numerous digital interventions (also referred to as "e-mental health" interventions) have been developed for the prevention and treatment of eating disorders and several meta-analyses have summarized the existing evidence on the efficacy and effectiveness of such interventions. Based on the present systematic review of McClure and Colleagues, the question of how and for whom digital interventions for eating disorders actually work, remains unanswered. In the absence of reliable mediators and moderators of outcome, priorities for future research are discussed (e.g., a need for more rigorous RCTs with credible comparators). The resulting research agenda is expansive. However, even though this process will take time and might seem slow (especially, in contrast to the rapidity of technological developments), we should not accept a lowering of the quality bar in research on digital interventions compared to other intervention research.